2009
DOI: 10.1071/en08078
|View full text |Cite
|
Sign up to set email alerts
|

Sources of antimony in an urban area

Abstract: Environmental context. The global production and use of antimony (Sb) increase together with stocks and emissions, but there are gaps in our knowledge concerning environmental effects. Here, a reconstruction of major Sb flows in an urban area was conducted. The major emission source of Sb identified was wear of brake linings, although other sources may also be of importance, e.g. diffuse emission of flame-retarded goods. Abstract. The present study sets out to analyse the urban metal sources of Sb, by estimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Factor 10 was characterized by a high abundance of Sb explaining 78% of the variation. Common airborne Sb sources are crustal material, brake dust, coal combustion, , carpets and clothing treated with Sb-containing flame retardant materials (SbO 3 and Sb 2 O 5 ). The ratio of Cu/Sb has been used to discriminate different airborne sources such as upper continental crust (64), traffic including brake dust (2.3–10.1), , coal fly ash (∼20), and carpet samples (0.18) . In this study, the ratio of Cu/Sb in indoor PM 1 samples was 0.04, suggesting an influence of resuspension of dust from flame retardant-treated carpet.…”
Section: Results and Discussionmentioning
confidence: 75%
“…Factor 10 was characterized by a high abundance of Sb explaining 78% of the variation. Common airborne Sb sources are crustal material, brake dust, coal combustion, , carpets and clothing treated with Sb-containing flame retardant materials (SbO 3 and Sb 2 O 5 ). The ratio of Cu/Sb has been used to discriminate different airborne sources such as upper continental crust (64), traffic including brake dust (2.3–10.1), , coal fly ash (∼20), and carpet samples (0.18) . In this study, the ratio of Cu/Sb in indoor PM 1 samples was 0.04, suggesting an influence of resuspension of dust from flame retardant-treated carpet.…”
Section: Results and Discussionmentioning
confidence: 75%
“…In addition, Adriano [1] reported Zn-Sn and Cd-Sn alloys as commonly used coatings in hydraulic brakes. Research by Månsson et al [112] in Stockholm, Sweden, also suggested that the main source of Sb emissions in an urban area is brake pad wear. Similarly, Clemente [3] suggested that the use of Sb as a fire retardant in brake pads emits significant amounts from vehicles into the environment.…”
Section: Anthropogenic Sources Of Soil Pollution With Sn and Sbmentioning
confidence: 96%
“…Numerous studies have addressed the problem with increasing amounts of chemicals in consumer products (Mao and Graedel ; Månsson et al ; Odukudu et al ; Vyzinkarova and Brunner ), but there is often a considerable lack of knowledge regarding the substances used in these products. One such product group is cosmetics.…”
Section: Introductionmentioning
confidence: 99%